Transcutaneous electrical nerve stimulation in speech therapy rehabilitation of voice and swallowing function in adults-a systematic review - Milena Assis daSilva; Laura Davison Mangilli (Wiley, 2021)
Abstract Introduction In recent years, a number of clinical trials have been published comparing transcutaneous electrical nerve stimulation (TENS) and traditional speech therapy treatment of voice and swallowing functions, but results have been conflicting. Objective Assess the methodological quality of studies and determine whether TENS is an efficient therapeutic strategy for speech therapy treatment of healthy adults or those with dysphonia and/or dysphagia. Methods The databases used were Medical Literature Analysis and Retrieval System Online (MedLine), Biblioteca Virtual em Saúde (BVS), Cochrane Library and Web of Science (ISI Web of Knowledge). The study was conducted between May 2018 and January 2019, in line with Cochrane Handbook guidelines, and included studies on the use of TENS in healthy adults or those with compromised voice and/or swallowing function. Results After the search and extraction of studies, the following were identified: TENS + VOICE: 7 articles; TENS + SWALLOWING: 5 articles. The studies exhibited medium quality and are heterogeneous, making it difficult to determine their effectiveness and the parameters to be used in future research. There were no statistically significant differences between the use of TENS alone or associated with another therapeutic technique for voice. For swallowing function, one study proved better results in cases of associated techniques - TENS + traditional therapy. Discussion Speech therapy should increase the number of studies published and improve their methodological quality, reassessing methodological criteria. Current clinical practice is not grounded in evidence‐based science. Clinical Message the studies analyzed exhibited medium methodological quality; there are variations in the time, number and periodicity of the therapeutic sessions for TENS; there were no statistically significant differences between the use of TENS alone or associated with another therapeutic technique in voice; there were statistically significant differences between the use of TENS associated with traditional therapeutic in swallowing function.